Investasi Safe Haven: Dampak Perang Rusia - Ukraina - Agustina Agustina; Andreani Caroline Barus (Owner : Riset dan Jurnal Akuntansi, 2023)
This research was conducted to determine the impact of the crisis caused by Russia and Ukraine on the condition of various war instrument investments, such as the stock market represented by the JCI and the Nasdaq Index, world gold prices, crypto assets such as bitcoin, Ethereum, ripple as well as against the US dollar. From these results, it is hoped that later the most stable investment instrument can be found when there is a crisis shock, so that it can provide input to investors to be able to make the safest investment. The study was conducted testing the difference between pre- and post-war conditions of Russia-Ukraine. The test uses a Wilcoxon test that is adjusted to the normality test results. Based on the tests carried out, it shows that there is a difference between the Stock Market (JCI); Stock Market (NASDAQ); Dollars; Crypto (Bitcoin); Crypto (Ethereum); Crypto (Ripple); World Gold before (Pre) with after (Post) Russia-Ukraine War.